Sustainable Solutions for Construction Waste Reduction in UAE - Yahya, Mina Muwafaq (2015)
The United Arab Emirates (UAE) is one of the biggest waste producers in the world and it is currently going through the challenge of realizing sustainability in construction and the conservation of the natural environment. The main problem has professed to be the management of waste from construction activities. The major causes of waste generation in UAE were the poor construction policies along with the lack of knowledge and awareness among all construction professionals and off-cuts resulting from planning and designing, thus; survey questioners were conducted for this research with goal of determining a series of solutions based on respondent’s opinion and experience during the construction sites. This research paper looks also into the current status of UAE waste generation in the construction industry and provides a comprehensive understanding on the current legislations and polices being implemented. This research proposes a sustainable package of solutions that will help to mitigate the amount of waste generated through different steps and actions need to be taken as part of the construction procedure. Interviews then incorporated to ensure the proposed solutions and its effectiveness from their perspective. Case study has been selected for this paper practicing the issue of controlling the waste by achieving the sustainability systems. It is evident that the presence of construction waste is a menace that needs to be eradicated. The main finding for this research is the lack of awareness that connected to several aspects which are the implementation of waste management plan and the governmental role. Construction companies and government agencies could partner to train them on the benefits of waste prevention and minimization and later offer incentives to construction firms that efficiently apply the acquired procedures in their design and implementation. The survey offers overwhelming positive responses on having a mandatory procedure of controlling the waste by the authority and increase the level of awareness. Waste minimization should be integrated and effectually implemented starting from the planning phase, design, through preparation, during and after implementation of the project. If all or parts of these solutions are implemented UAE can experience drastic reduction in construction waste thus; economic, social and environmental benefits will be established.